Microparticulated Mefenamic Acid with High Dispersion Stability for Pediatric Dosage Form - Moe Yamazaki; Emi Shimamura; Takehisa Hanawa; Yayoi Kawano (MDPI AG, 2022)
Mefenamic acid (MFA), a water-insoluble drug, is used as a suspension in the medical field, but it requires shaking before using to disperse MFA content in the suspension. In previous studies, trials to prepare MFA suspension with high dispersion stability by atomizing MFA by the wet-milling method. However, HPC is used for atomizing MFA. Therefore, the optimum concentration and molecular weight for atomizing MFA have not been investigated. In this study, we investigated the optimum molecular weight and concentration of HPC for the micronization of MFA. As a result, MFA particles became fine particles by adding SDS, and the particle size was also smaller than that of HPC alone. In addition, the suspension with the highest dispersion stability can be obtained when a mixed solution of 1.0% HPC-SL and 0.12% SDS aqueous solution is used. Therefore, this study considers that the addition of SDS and 1.0% HPC-SL aqueous solution are optimal for improving the dispersion stability of the MFA suspension.